2013
DOI: 10.3923/pjbs.2013.1046.1050
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Examination of Inflammation and Angiogenesis in the Pathogenesis of Primary Moderate Pterygium in a Well-designed Case-control Study

Abstract: Pterygium is a common ocular lesion whose exact etiology is a point of contention. Chronic inflammation and angiogenesis are two major proposed mechanisms of the disease in the current literature. The objective of this study is to examine these two mechanisms in a very well-designed setting. In a case-control study, 24 tissue specimens from the patients with primary moderate pterygium (cases) and 15 specimens excised from the nasal bulbar region in healthy counterparts (controls) were compared in terms of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
10
0
3
Order By: Relevance
“…1,2 Many ocular surface diseases such as dry eye, Stevens-Johnson syndrome, mucous membrane pemphigoid, chemical/thermal burns, pterygium, and vitamin A deficiency often show chronic inflammation of the ocular surface. [3][4][5][6] Chronic inflammation can lead to squamous metaplasia of the ocular surface epithelium through a signaling pathway. Squamous metaplasia may, in turn, exacerbate inflammation by dysfunction or loss of cells responsible for tear secretion.…”
mentioning
confidence: 99%
“…1,2 Many ocular surface diseases such as dry eye, Stevens-Johnson syndrome, mucous membrane pemphigoid, chemical/thermal burns, pterygium, and vitamin A deficiency often show chronic inflammation of the ocular surface. [3][4][5][6] Chronic inflammation can lead to squamous metaplasia of the ocular surface epithelium through a signaling pathway. Squamous metaplasia may, in turn, exacerbate inflammation by dysfunction or loss of cells responsible for tear secretion.…”
mentioning
confidence: 99%
“…The other cause of ECD decrease in eyes with pterygium is a variety of pathogenic factors including inflammation, angiogenesis and extracellular matrix modulators [9]. These modulators have been shown to be expressed in pterygium tissue or the cornea underlying or adjacent to the pterygium [7, 20]. Moreover, the levels of these pathogenic factors may be correlated with the clinical features of the pterygium [2122].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found many inflammatory mediators have been shown to induce angiogenesis in vivo, such as interleukins (IL)-6, -8 and -32, prostaglandins E (PGE)1 and PGE2, tumor necrosis factor-α (TNF-α) and nitric oxide (NO). [53][54][55] The expression of IL-6 is associated with early angiogenic events and thus has been implicated in angiogenesis, but in vitro it has demonstrated dual effects on EC growth (IL-6 can both promote and inhibit the proliferation of EC), which make its role difficult to appreciate. 56,57 IL-8 is a well-known inflammatory chemokine, and it is propitious to the proliferation and migration of EC.…”
Section: Effects Of Inflammation On the Angiogenesis Are Mainly Reflementioning
confidence: 99%